2018
DOI: 10.22456/1679-9216.83864
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Viral Etiopathogenesis in Lambs and Goat Kids with Neonatal Diarrhea

Abstract: Background: Neonatal enteritis is an important disease that causes deaths of animals before 3 weeks of age, and results in significant economic losses. Viral agents can predispose the young animals to secondary infections in the gastrointestinal tract, especially in lambs and goat kids younger than 21 days. Although the neonatal diarrhea is common in calves, there is still little knowledge about pathology, pathogenesis and immunohistochemical localization of viral agents that cause neonatal enteritis in lambs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Yatoo et al ( 25 ) have reported neonatal diarrhea usually occurs during spring season from March to May and was corroboration with Parray et al ( 26 ). Mortality rates of neonatal diarrhea depended on management and epidemic prevention conditions and varied 25–50% ( 27 ) and was 14.3% in the present study carried out from March to July in a small local family farm. And in this study, we showed that neonate goats with diarrhea exhibited an oxidative stress status in the intestine as evidenced by an increase in the MDA level and a decrease in GSH-Px level.…”
Section: Discussionmentioning
confidence: 63%
“…Yatoo et al ( 25 ) have reported neonatal diarrhea usually occurs during spring season from March to May and was corroboration with Parray et al ( 26 ). Mortality rates of neonatal diarrhea depended on management and epidemic prevention conditions and varied 25–50% ( 27 ) and was 14.3% in the present study carried out from March to July in a small local family farm. And in this study, we showed that neonate goats with diarrhea exhibited an oxidative stress status in the intestine as evidenced by an increase in the MDA level and a decrease in GSH-Px level.…”
Section: Discussionmentioning
confidence: 63%